On Minimum Wiener Polarity Index of Unicyclic Graphs with Prescribed Maximum Degree - Jianping Ou; Xing Feng; Saihua Liu (Journal of Applied Mathematics)
The Wiener polarity index of a connected graph G is defined as the number of its pairs of vertices that are at distance three. By introducing some graph transformations, in different way with that of Huang et al., 2013, we determine the minimum Wiener polarity index of unicyclic graphs with any given maximum degree and girth, and characterize extremal graphs. These observations lead to the determination of the minimum Wiener polarity index of unicyclic graphs and the characterization of the extremal graphs.